-2z+4=-27.2+2z

Simple and best practice solution for -2z+4=-27.2+2z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2z+4=-27.2+2z equation:


Simplifying
-2z + 4 = -27.2 + 2z

Reorder the terms:
4 + -2z = -27.2 + 2z

Solving
4 + -2z = -27.2 + 2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-2z' to each side of the equation.
4 + -2z + -2z = -27.2 + 2z + -2z

Combine like terms: -2z + -2z = -4z
4 + -4z = -27.2 + 2z + -2z

Combine like terms: 2z + -2z = 0
4 + -4z = -27.2 + 0
4 + -4z = -27.2

Add '-4' to each side of the equation.
4 + -4 + -4z = -27.2 + -4

Combine like terms: 4 + -4 = 0
0 + -4z = -27.2 + -4
-4z = -27.2 + -4

Combine like terms: -27.2 + -4 = -31.2
-4z = -31.2

Divide each side by '-4'.
z = 7.8

Simplifying
z = 7.8

See similar equations:

| c=clt | | c=cult | | c=cly | | 5logx=8 | | -81=b-3(7-3b) | | 22=(x-300000)/x | | 7x=-45 | | k=8r-s | | 0.45(6)+0.05x=0.15(12+x) | | 2z+1.1=0+3z | | 120=x+(x-3) | | 10-(2y-4)=7-3y | | 2x^2-242= | | 3m^4+18m^2-120=0 | | 3v+30=-3(v+2) | | 4x^2+20x+106=0 | | (4y^2-5y^3)-(6y^2+5y+7)= | | 2z^2-z-1=0 | | -7y+2(y-7)=1 | | a*25/2=-5/8 | | 4-3(y+2)=16 | | 1/4(9x-8) | | 1-15*x+3*x^2+x^3=0 | | 294=3-y | | 2r-5r+7+r= | | 2x^4+2x^2-180=0 | | b^2-8b-0= | | 10+7x+x^2=0 | | 2u=-14 | | 5(z-21)=9(z+15) | | 0.20x+0.25(70)=33.5 | | 2w^4-28w^3+96w^2= |

Equations solver categories